Penyusunan Laporan Keuangan berdasarkan SAK EMKM (Studi Kasus pada UMKM Pangkalan LPG UD. Ahmad Baihaqi di Kuala Pembuang) - Noor Sentya Wati; Sigit Mulyanto (Keizai, 2021)
The purpose of this study was to determine the preparation of financial statements based on SAK EMKM at LPG Base UD. Ahmad Baihaqi provides benefits for preparing reports according to accounting standards, such as making it easier for MSME owners to make economic decisions. The descriptive-qualitative research method was used in this study. Sources of data are primary data and secondary data. The results of the research that has been carried out from January 1 to March 31, 2021, are in the form of a statement of financial position showing assets, liabilities, and equity of IDR 71,915,250, an income statement showing a profit of IDR 8,647,000 and notes on the LPG Base financial statements. UD. Ahmad Baihaqi.